Features of water chemical composition of oligotrophic and eutrophic bogs in the South of the Tomsk region; IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Naymushina O. S. Olga Sergeevna (Hydrogeochemistry, 2016)
Title screen